Glycation in Alzheimer’s Disease and Type 2 Diabetes: The Prospect of Dual Drug Approaches for Therapeutic Interventions - Sama Ayoub (15430987) (2025)
As global life expectancy increases, the prevalence of neurodegenerative diseases like Alzheimer’s disease (AD) continues to rise. Since therapeutic options are minimal, a deeper understanding of the pathophysiology is essential for improved diagnosis and treatments. AD is marked by the aggregation of Aβ proteins, tau hyperphosphorylation, and progressive neuronal loss, though its precise origins remain poorly understood. Meanwhile, type 2 diabetes mellitus (T2DM) is characterized by chronic hyperglycemia, leading to the formation of advanced glycation end products (AGEs), which are implicated in tissue damage and neurotoxicity. These AGEs can be resistant to proteolysis and, therefore, accumulate, exacerbating AD pathology and accelerating neurodegeneration. Insulin resistance, a hallmark of T2DM, further complicates AD pathogenesis by promoting tau hyperphosphorylation and Aβ plaque accumulation. Additionally, gut microbiome dysbiosis in T2DM fosters AGE accumulation and neuroinflammation, underscoring the intricate relationship between metabolic disorders, gut health, and neurodegenerative processes. This complex interplay presents both a challenge and a potential avenue for therapeutic intervention. Emerging evidence suggests that antidiabetic medications may offer cognitive benefits in AD, as well as in other neurodegenerative conditions, pointing to a shared pathophysiology. Thus, we posit that targeting AGEs, insulin signaling, and gut microbiota dynamics presents promising opportunities for innovative treatment approaches in AD and T2DM. Other Information Published in: Molecular Neurobiology License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s12035-025-05051-9